ANALISIS TEKNIK PENERJEMAHAN SUBTITLE BAHASA ARAB KE BAHASA INDONESIA PADA FILM PENDEK AKUN INSTAGRAM @arabiyahtalks - Muhammad Arifin Ilham; Abdul Majid; Hanifah Nurfitri; Rinaldi Supriadi (PT. CASA CENDEKIA MEDIA, 2025)
This research aims to analyze the subtitle translation techniques from Arabic to Indonesian in short film content published on the Instagram account @arabiyahtalks. As part of the translation process, the techniques used in this study include reduction, amplification, transposition, and modulation. These techniques are applied to ensure that the message conveyed remains understandable to the Indonesian audience without sacrificing the meaning or original style of the Arabic language. The research data were obtained through the documentation of content from the Instagram account, which was then analyzed to identify various translation techniques used. The research results show that the translator successfully overcame the challenges arising from language and cultural differences, and was able to convey a message that aligns with the cultural context of the target audience. Thus, this research emphasizes the importance of using appropriate translation techniques to ensure message accuracy and smooth communication across languages and cultures